2022
DOI: 10.3390/plants11212932
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Forest Net Primary Productivity to Climatic Factors in China during 1982–2015

Abstract: Forest ecosystems play an important role in the global carbon cycle. Clarifying the large-scale dynamics of net primary productivity (NPP) and its correlation with climatic factors is essential for national forest ecology and management. Hence, this study aimed to explore the effects of major climatic factors on the Carnegie–Ames–Stanford Approach (CASA) model-estimated NPP of the entire forest and all its corresponding vegetation types in China from 1982 to 2015. The spatiotemporal patterns of interannual var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
17
1
Order By: Relevance
“…The reason was that the enhanced solar radiation made vegetation accept more light, photosynthesis was strengthened, and the accumulation of dry matter in vegetation was increased. The study was found that the effect of solar radiation on different vegetation types were different, and the effect of solar radiation on forests was stronger than that on precipitation and temperature (Du et al, 2022). In addition, it has been found that NPP is negatively correlated with solar radiation in most areas of the Loess Plateau (Xie et al, 2014), which was not consistent with the conclusion that NPP was mainly affected by solar radiation obtained in this paper.…”
Section: Relationship Between Npp and Climate Factorscontrasting
confidence: 67%
See 1 more Smart Citation
“…The reason was that the enhanced solar radiation made vegetation accept more light, photosynthesis was strengthened, and the accumulation of dry matter in vegetation was increased. The study was found that the effect of solar radiation on different vegetation types were different, and the effect of solar radiation on forests was stronger than that on precipitation and temperature (Du et al, 2022). In addition, it has been found that NPP is negatively correlated with solar radiation in most areas of the Loess Plateau (Xie et al, 2014), which was not consistent with the conclusion that NPP was mainly affected by solar radiation obtained in this paper.…”
Section: Relationship Between Npp and Climate Factorscontrasting
confidence: 67%
“…Therefore, deciduous coniferous forests are widely distributed in this region, and the NPP of deciduous coniferous forests was lower than that of evergreen broad-leaved forests. Therefore, the NPP in the northwestern MRYR was low (Du et al, 2022). At present, there are relatively few research results on the inhibitory effect of precipitation on NPP, mainly on the Qinghai-Tibet Plateau .…”
Section: Relationship Between Npp and Climate Factorsmentioning
confidence: 99%
“…We investigated the spatiotemporal changes in forest NPP in China from 2001 to 2017. NPP was calculated based on the CASA model, although its prediction accuracy is not perfect due to the differences in spatial resolution and the actual and simulated values of variable factors [ 22 ]. Nevertheless, it is widely recognized and applied in numerous macroecological studies [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPP data from 2000 to 2017 were obtained at a 250 × 250 m resolution from NASA ( ) (accessed on 10 October 2022). The Carnegie-Ames-Stanford Approach (CASA) model was used to estimate NPP as follows [ 22 ]: where APAR ( x , t ) represents the photosynthetically active radiation (PAR, in units of MJ/m 2 ) absorbed at pixel x in month t , and ε ( x , t ) represents the actual light energy utilization at pixel x in month t (g C/MJ).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…First, the statistical model-based method. This approach analyses the relative contribution depending on the linear correlation between NPP and its influencers (Du et al, 2022; Yang et al, 2017). It is a simple method but cannot portray the complex nonlinear relationship between NPP and its influencers well (Liu et al, 2020; Turner and Carpenter, 2017).…”
Section: Introductionmentioning
confidence: 99%